PEMANFAATAN PEMBELAJARAN DIFERENSIASI DALAM MATA PELAJARAN INFORMATIKA UNTUK MENDUKUNG KURIKULUM MERDEKA - Ardiansyah, Lucky; Handayani, Anik Nur; Srini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to enhance student engagement, participation, and comprehension through differentiated instruction based on gamification using the Wordwall and Kahoot platforms in Informatics lessons for 7th-grade students at SMPN 22 Malang. The research employed Classroom Action Research (CAR) with both qualitative and quantitative approaches conducted over multiple cycles. The findings indicate that this strategy effectively increased student involvement, as evidenced by higher observation scores and improved post-test results. Most students responded positively to technology-based learning, particularly in terms of activeness and participation. Challenges included technical issues and student adaptation to the new method, which were mitigated through early technical assistance, simplified instruction, and personalized support. Gamified learning created a more engaging and enjoyable classroom environment and supported the implementation of Kurikulum Merdeka, which accommodates diverse student needs. The outcomes contribute to the development of more innovative and responsive teaching strategies in Informatics and serve as a model for similar implementations in other schools.